(untitled) (Indian Journal of Nematology, 2024)
Compatibility of indigenous entomopathogenic nematode, Steinernema abbasi (CISH EPN-1) with nine insecticides (Profenophos 50% EC, Lambda-cyhalothrin 5% EC, Dimethoate 30% EC, Quinalphos 25% EC, Chlorfenapyr 10% SC, Chlorantranilprole 18.5% SC, Dichlorvos 76% EC, Bifenthrin 8% SC and Spinosad 45% SC) was evaluated (at field recommended doses) under laboratory conditions. Out of the tested chemicals, Spinosad and Bifenthrin had no adverse effects on the survival of infective juveniles but those exposed to Dichlorvos showed significantly higher mortality (100%) within 72 hours after treatment, whereas, with rest of the insecticides, mortality ranged between 36-90%. Further, the virulence tests revealed that infective juveniles exposed to Spinosad, Bifenthrin, Dimethoate and Lambda-cyhalothrin retained their ability to infect final instar larvae of greater wax moth, Galleria mellonella, thus, exhibiting good compatibility and favoring S. abbasi as a potential EPN against mango pests as an integral part of eco-friendly pest management system.